On the possibility, unity and systematic character of experience, in the light of the principle of finality in nature in Kant's Critique of judgement - Carrillo Castillo, Lucy (Estudios de Filosofía, 1994)
The article is a commentary on one of the basic thesis of the introduction to the Critique of Judgment. The fundamental activity of the faculty of judgment is reflection, mediating between what is conditioned (nature) and what is unconditioned (freedom). Reflection is not knowledge, but without it knowledge is impossible. This question is present in the concepts of nature and experience; together with the concept of nature transcendental reflection must establish the idea of a unity and totality of experience, in order to adjust our cognitive faculties to the object of knowledge. But such an act of reflection implies the admission of a principie of finality in nature, analogous to the realm of freedom. This idea of teleology guides human thought, experience and culture, subordinating knowledge to morality.